Relation of Nailfold Capillaries and Autoantibodies to Mortality in Patients With Raynaud Phenomenon. Issue 5 (2nd February 2016) - Mueller, Markus; Gschwandtner, Michael E.; Gamper, Jutta; Giurgea, Georgiana-Aura; Charwat-Resl, Silvia; Kiener, Hans P.; Smolen, Josef S.; Perkmann, Thomas; Koppensteiner, Renate; Schlager, Oliver
Abstract : Background—: In incipient Raynaud phenomenon, nailfold capillaroscopy and autoantibody tests are obtained to screen for an emerging connective tissue disease. Whether the presence of abnormal nailfold capillaries and autoantibodies are related to mortality in patients with incipient Raynaud phenomenon is not known. Methods and Results—: In 2958 consecutive patients (78% women, median age 45 years) with incipient Raynaud phenomenon without previously known connective tissue disease, nailfold capillaroscopy and laboratory tests for antinuclear antibodies (ANA) and ANA subsets were obtained at initial presentation. During a median follow-up period of 9.3 years, 227 women (9.9% of female patients) and 129 men (20% of male patients) with Raynaud phenomenon died. In comparison with a demographically matched standard population, survival was poorer in patients with Raynaud phenomenon (log-rank test P <0.0001). In patients with Raynaud phenomenon, mortality was higher in men than in women ( P <0.0001, Cox proportional hazards model). In women, the presence of abnormal nailfold capillaries, ANA, and anti–Scl-70 antibodies were related to an increase in all-cause mortality. The conjoint presence of abnormal nailfold capillaries and autoantibodies was associated with the highest mortality rates. In men, abnormal nailfold capillaries, and ANA and ANA subsets, as well, were not related to survival. In both sexes, patients' age and serum creatinine were associated with mortality. Conclusions—: In Raynaud phenomenon, male sex, age, and serum creatinine are related to mortality. Abnormal nailfold capillaries and autoantibodies are associated with an increase in all-cause mortality in female patients, but not in male patients with Raynaud phenomenon. Abstract : Supplemental Digital Content is available in the text.